2013
DOI: 10.3892/ijo.2013.2134
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia reduces CD138 expression and induces an immature and stem cell-like transcriptional program in myeloma cells

Abstract: Although CD138 expression is a hallmark of plasma cells and myeloma cells, reduced CD138 expression is occasionally found. However, the mechanisms underlying CD138 downregulation in myeloma cells remain unclear. Previous reports suggest that the bone marrow microenvironment may contribute to CD138 downregulation. Among various factors in the tumor microenvironment, hypoxia is associated with tumor progression, poor clinical outcomes, dedifferentiation and the formation of cancer stem cell niches in solid tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 46 publications
3
63
1
1
Order By: Relevance
“…For personal use only on March 25, 2019. by guest www.bloodadvances.org From under chronic hypoxia and prevents cell proliferation and cell maturation. Expression of IRF4 is suppressed in hypoxic environments, 7,9 although IRF4 is a key factor in promoting myeloma oncogenesis. 16 Therefore, it is likely that during hypoxia, factors that contribute to myeloma cell survival may act independent of IRF4.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For personal use only on March 25, 2019. by guest www.bloodadvances.org From under chronic hypoxia and prevents cell proliferation and cell maturation. Expression of IRF4 is suppressed in hypoxic environments, 7,9 although IRF4 is a key factor in promoting myeloma oncogenesis. 16 Therefore, it is likely that during hypoxia, factors that contribute to myeloma cell survival may act independent of IRF4.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that myeloma cells change their surface antigens and metabolic pathways in response to hypoxic stress, and they also acquire drug resistance. 7,8 In addition, we recently reported that miR-210, whose expression is markedly elevated in a hypoxic environment, downregulates IRF4 through the direct regulation of an 18S rRNA base methyltransferase, DIMT1. 9 These findings led us to conclude that miR-210 suppresses IRF4 expression .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,26 Hypoxia promotes immature and stem-cell like phenotype in myeloma cells by decreasing CD138 and increasing CD34 expression. 9,39 Such hypoxic cells are resistant to proteasome inhibitors including bortezomib and carfilzomib. 9 In accordance to these studies, our results showed that hypoxic RPMI8226 and U266 cells became resistant to bortezomib compared to their normoxic counterparts.…”
Section: Discussionmentioning
confidence: 99%